Income redistribution through taxes and transfers across OECD countries - Causa, Orsetta; Hermansen, Mikkel (Paris, 2017)
"This paper produces a comprehensive assessment of income redistribution to the working-age population, covering OECD countries over the last two decades. Redistribution is quantified as the relative reduction in market income inequality achieved by personal income taxes, employees’ social security contributions and cash transfers, based on household-level micro data. A detailed decomposition analysis uncovers the respective roles of size, tax progressivity and transfer targeting for overall redistribution, the respective role of various categories of transfers for transfer redistribution; as well as redistribution for various income groups. The paper shows a widespread decline in redistribution across the OECD, both on average and in the majority of countries for which data going back to the mid-1990s are available. This was primarily associated with a decline in cash transfer redistribution while personal income taxes played a less important and more heterogeneous role across countries. In turn, the decline in the redistributive effect of cash transfers reflected a decline in their size and in particular by less redistributive insurance transfers. In some countries, this was mitigated by more redistributive assistance transfers but the resulting increase in the targeting of total transfers was not sufficient to prevent transfer redistribution from declining."